Pengaruh Pendidikan Gizi Terhadap Tingkat Pengetahuan Gizi Seimbang Pada Siswa - Arief Fardiansyah; Sulis Diana; Dlia Usratul Khoiriyah (Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2026)
Nutritional problems among school-age children remained an important public health issue, characterized by the presence of both undernutrition and overnutrition, which could affect children’s health and development. Low knowledge of balanced nutrition was one of the factors influencing students’ eating behavior. Therefore, nutrition education using educational game-based media was needed to effectively improve students’ understanding. This study used a quasi-experimental design with a pretest-posttest control group approach. The study population consisted of 93 students in grades IV, V, and VI at SDN Pulorejo 2, with a sample of 48 students selected using stratified proportionate random sampling. The sample was divided into two groups: the smart dice media group and the true-false card media group. Data were collected using a questionnaire that had been tested for validity and reliability, and were analyzed using the Paired Sample T-Test and Independent Sample T-Test. The results showed that there was a significant increase in balanced nutrition knowledge in both groups (p < 0.05). The mean knowledge score in the smart dice group increased from 74.79 to 86.63, while in the true-false card group it increased from 70.21 to 80.54. Comparative analysis showed a significant difference in post-test results (p = 0.032), where the smart dice group demonstrated a higher improvement. Nutrition education based on educational games was proven to be effective in improving students’ knowledge. The smart dice media was more effective due to its higher level of interactivity, which enhanced student engagement and understanding.